Real-world evidence of tisagenlecleucel for pediatric acute lymphoblastic leukemia and non-Hodgkin lymphoma - Pasquini, Marcelo C.; Hu, Zhen-Huan; Curran, Kevin; Laetsch, Theodore; Locke, Frederick; Rouce, Rayne; Pulsipher, Michael A.; Phillips, Christine L.; Keating, Amy; Frigault, Matthew J.; Salzberg, Dana; Jaglowski, Samantha; et al. (Blood advances, 2020)
Tisagenlecleucel is a CD19 chimeric antigen receptor (CAR) T-cell therapy approved for treatment of pediatric and young adult patients with relapsed/refractory acute lymphoblastic leukemia (ALL) and adults with non-Hodgkin lymphoma (NHL). The initial experience with tisagenlecleucel in a real-world setting from a cellular therapy registry is presented here. As of January 2020, 511 patients were enrolled from 73 centers, and 410 patients had follow-up data reported (ALL, n = 255; NHL, n = 155), with a median follow-up of 13.4 and 11.9 months for ALL and NHL, respectively. Among patients with ALL, the initial complete remission (CR) rate was 85.5%. Twelve-month duration of response (DOR), event-free survival, and overall survival (OS) rates were 60.9%, 52.4%, and 77.2%, respectively. Among adults with NHL, the best overall response rate was 61.8%, including an initial CR rate of 39.5%. Six-month DOR, progression-free survival, and OS rates were 55.3%, 38.7%, and 70.7%, respectively. Grade ≥3 cytokine release syndrome and neurotoxicity were reported in 11.6% and 7.5% of all patients, respectively. Similar outcomes were observed in patients with in-specification and out-of-specification products as a result of viability <80% (range, 61% to 79%). This first report of tisagenlecleucel in the real-world setting demonstrates outcomes with similar efficacy and improved safety compared with those seen in the pivotal trials. •Represents the largest set of safety and efficacy data for tisagenlecleucel.•Outcomes in the real-world setting are similar to results in the pivotal trials. [Display omitted]